Displacement measurement of soft material indentation using light intensity - Mohd Nadzeri, Omar; Mohd Hasnun Ariff, Hassan (UiTM Press, 2022)
This paper studies proof of concept in which soft material displacement during indentation is measured by a change in light intensity as the indenter is pushed into a soft material. The Light Dependent Resistor (LDR) sensor, which is embedded within a transparent hemispheric indenter, is used to measure the intensity of light while the indenter is on the surface and within the soft material. The change in light intensity contributes to a gradient that can be used to calculate the displacement of the soft material. The calculated difference in light intensity is converted into a displacement with the mean conversion factor obtained from the calibration equation. Measurements were carried out on three silicone samples with varying elastic properties over a range of different light intensities. By referring to linear regression and Rsquared values, the proposed concept has high consistency in measuring the difference of light intensity for various materials at different initial light intensities with more than 95% of R-squared values. In addition, the mean of variance between measurements, reflecting repeatability, is within an outstanding 1.5%. In the meantime, the accuracy of the proposed concept tested concerning the actual displacement is less than 10% of the variation. With promising results, the proposed design can be applied as a standalone technology or as an extension to a hand-held soft material characterization device for further improvement.